2019
DOI: 10.1088/1742-6596/1273/1/012076
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Temperature Distribution and Structural Deformation of the Car Dashboard Subjected to Direct Sunlight

Abstract: A situation in which the car is directly parked under the sunlight needs to be considered as one of unavoidable operating conditions.The thermal phenomenon perceived by car dashboard might affect its functionality. The biomechanical function of the dashboard focused on the thermo-structural evaluation due to the direct sunlight was numerically simulated and investigated in this work. Polypropylene was chosen as the main dashboard material.The aims are to evaluate the temperature distribution, stress distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Based on several experts' opinions about evaluation (Adnan et al, 2019;Andrade, 2019;Chen, 2017;Gu, 2020;JH & Baderiah, 2020;Ratminingsih et al, 2018;Wirawan et al, 2018;Yahiji et al, 2019;Yudianto et al, 2019), it can be concluded that evaluation is an activity planned to assess the achievement of a program for decision making. In addition, it is stated by Republic of Indonesia Law Number 20/2003 article 57 paragraph (1) on the National Education System that evaluation is carried out in order to control the quality of education nationally as a form of teachers' and institutions' accountability to interested parties.…”
Section: Discussionmentioning
confidence: 99%
“…Based on several experts' opinions about evaluation (Adnan et al, 2019;Andrade, 2019;Chen, 2017;Gu, 2020;JH & Baderiah, 2020;Ratminingsih et al, 2018;Wirawan et al, 2018;Yahiji et al, 2019;Yudianto et al, 2019), it can be concluded that evaluation is an activity planned to assess the achievement of a program for decision making. In addition, it is stated by Republic of Indonesia Law Number 20/2003 article 57 paragraph (1) on the National Education System that evaluation is carried out in order to control the quality of education nationally as a form of teachers' and institutions' accountability to interested parties.…”
Section: Discussionmentioning
confidence: 99%
“…It is a numerical technique discretizing a model into small elements and reconnects the elements at points called nodes. It has also been widely employed to investigate various problems in mechanical engineering (Karthikeyan, Rajkumar, Bensingh, Kader, & Nayak, 2020;Yudianto, Ghafari, Huet, & Wakid, 2019), medical devices (Barkaoui, Ait Oumghar, & Ben Kahla, 2021), biomedical engineering (Lisiak-Myszke et al, 2020), safety engineering (Yudianto, Prasetyono, Adiyasa, Purnomo, & Fauzi, 2020), and civil engineering (Pelekis, McKenna, Madabhushi, & DeJong, 2021;Ren, Fan, Li, & Chen, 2019). The use of finite element analysis has also been firmly validated, leading to the proof that the methodology has been used and applicable for engineering research and acceptable in various cases of engineering (Bola, Simões, & Ramos, 2021;López-Campos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The flow becomes more intricate when two road vehicles are in the overtaking process. As a result, the aerodynamic forces imposed on the vehicles vary as the position of the vehicles during the overtaking process changes which affects the vehicle's stability and safety [1][2][3][4][5][6]. Moreover, a crosswind causes problems for the vehicle's motion and drivability since there are additional lateral air velocity components [7].…”
Section: Introductionmentioning
confidence: 99%